2004
DOI: 10.1021/jf048878n
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Citrinin Occurrence and Cytotoxicity in Monascus Fermentation Products

Abstract: Monascus purpureus and its fermentation products have been used in food coloring and meat preservation in Asia for centuries and have also been recently used as dietary supplements because of their cholesterol-lowering ability. However, the presence of the mycotoxin citrinin (CTN), a secondary metabolite of Monascus species, in fermentation products is a potential threat to public health. In the present study, HPLC was used to analyze CTN levels in lipid and aqueous extracts of commercialized Monascus products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 36 publications
4
66
0
Order By: Relevance
“…CTN contamination has additionally been reported in Monascus fermentation products [29,37] used as food colourants and flavour enhancers in the Orient, and as dietary supplements believed to prevent heart disease and decrease plasma triacylglycerol and cholesterol levels [38]. One recent study identified 0.28-6.29 µg/g CTN in lipid extracts from commercialized Monascus products [29], while another showed that treatment of human HEK-293 cells (human embryonic kidney cells) with lipid extracts of Monascus products (60 µM CTN) for 72 h induced over 50 % cell death [29]. As these and other studies have shown that CTN can induce apoptosis, I examined the effects of 30 µM CTN (∼ 3.75 µg/g in culture medium) on blastocysts in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CTN contamination has additionally been reported in Monascus fermentation products [29,37] used as food colourants and flavour enhancers in the Orient, and as dietary supplements believed to prevent heart disease and decrease plasma triacylglycerol and cholesterol levels [38]. One recent study identified 0.28-6.29 µg/g CTN in lipid extracts from commercialized Monascus products [29], while another showed that treatment of human HEK-293 cells (human embryonic kidney cells) with lipid extracts of Monascus products (60 µM CTN) for 72 h induced over 50 % cell death [29]. As these and other studies have shown that CTN can induce apoptosis, I examined the effects of 30 µM CTN (∼ 3.75 µg/g in culture medium) on blastocysts in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…While CTN clearly induces apoptosis in mammalian cells [28,29], its effects on embryonic development and the precise regulatory mechanisms governing these effects are currently unclear. To identify the apoptotic signalling pathway(s) involved in CTNinduced cell death in embryonic cells, I initially analysed the effects of the toxin on embryonic stem cells (ESC-B5) in vitro.…”
Section: The Effects Of Ctn On Esc-b5 Cellsmentioning
confidence: 99%
“…The toxic effects of citrinin observed in vitro were reported in HEK 293 cells (Liu et al, 2005), mouse embryonic stem cells (Chan, 2008), CHO-K1 cells (Liu et al, 2003), and V79 cells (Pfeiffer et al, 1998). These studies used 10-100 μM citrinin to assess the toxic effects, with lower concentrations having no signifi cant effect (Pfeiffer et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological effects of citrinin, a secondary metabolite produced by several fungal species including Monascus sp. and Penicillium sp., have been reported, including increasing apoptosis and decreasing the number and viability of treated cells (Liu et al, 2005;Chan and Shiao, 2007). Citrinin increased DNA fragmentation in HL-60 cells (Yu et al, 2006), which might lead to a reduction of the muscle RNA (Table 3) thereby inducing lower cell proliferation (Chan and Shiao, 2007).…”
Section: Effect Of Red Monascal Rice Supplementation On Growthmentioning
confidence: 97%
“…This compound has been found to induce reproductive abnor-malities in male gametes (Qingqing et al, 2012), and to reduce the rate of oocyte maturation and fertilization (Chan, 2008); it also has a teratogenic effect (Chan and Shiao, 2007;Singh et al, 2007a;Chan, 2008), and has induced maternal toxicity in pregnant rats (Singh et al, 2007b). Moreover, it has been associated with cytoto-xicity (Liu et al, 2005) and the activation of apoptosis by the mitochondrial pathway (Yu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%